COVID-19 vaccine trials in Africa (2020)
On Aug 17, 2020, screening began for participants to enrol in the mid-stage study of an experimental COVID-19 vaccine by Novavax, a US drug developer of next-generation vaccines for serious infectious diseases, at Witwatersrand University (Wits) in Johannesburg, South Africa. A US$15 million grant towards the trial was awarded to Novavax by the Bill & Melinda Gates Foundation. 2665 healthy adults and nearly 240 medically stable, HIV-positive adults will be enrolled.